Gendered worlds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
One Wougnet partner is running an (actual) international conference on 'Gendered Worlds: an African perspective', in Kampala from 21 to 26 July 2002. The focus includes young voices and genderising women and men. Women s Worlds 2002Women and Gender...